Electrochemical sensors based on TiO2–Fe2O3 coupled system - Anna Kusior; Iwona Karoń; Marta Radecka (Metrology and Measurement Systems, 2020)
Recently, transition metal oxides, which exhibit favorable catalytic abilities, have also been investigated as a material for the detection of hydrazine (N2H4). It has been reported that mixed metal oxides usually offer a higher electrochemical activity than binary oxides. In this work, a TiO2–Fe2O3 coupled system is presented as an enhanced material with major applications in electrochemical detectors. The electrochemical behavior of glassy carbon electrodes modified with TiO2–Fe2O3 in the absence and presence of hydrazine was evaluated via cyclic voltammetry (CV). Experimental results also suggest that the formation of the TiO2– Fe2O3 coupled system enhances electrochemical catalytic performance in N2H4 detection. The modification TiO2 + 2 mol% Fe2O3 provides good analytical performance of detection (0.13 mM) and quantification limits (0.39 mM). The presented coupled system provides the premise for a suitable material for a stable and sensitive N2H4 sensor.